Integration of embedded software with corporate information systems - Machado, Ricardo J. (2005)
This paper describes a methodology and corresponding tools to support the development of information systems, by integrating and interconnecting a network of embedded devices, that supervise processes in industrial environments, with the corporate information system of an organization. We discuss in detail how the LabVIEW environment was customized, so that it effectively supports a component based and data flow approach in the development of the gateway responsible for the integration.